THE INFLUENCE OF SYSTEMAL THINKING AND CONCEPT OF THE QUR'AN AND HADITH ON THE DEVELOPMENT AND IMPROVEMENT OF QUALITY MANAGEMENT OF ISLAMIC EDUCATION - Susrianto, Doni; Kemas Imron Rosadi (Dinasti Publisher, 2022)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews the development and improvement of quality management of Islamic education: The Effect of Systematic Thinking and Conceptions of the Qur'an and Hadith, a Literature Study of Human Resource Management. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this research library are that: 1) Systems Thinking has an effect on Development; 2) Conception of Al-Qur'an and Hadith influence the Development; 3) Systematic Thinking has an effect on improving the quality management of Islamic education; 4) The conception of the Qur'an and Hadith has an effect on improving the quality management of Islamic education; and 5) Development has an effect on improving the quality management of Islamic education.